Whale lice (Isocyamus deltobranchium & Isocyamus delphinii; Cyamidae) prevalence in odontocetes off the German and Dutch coasts – morphological and molecular characterization and health implications. (August 2021) - Lehnert, Kristina; IJsseldijk, Lonneke L.; Uy, May Li; Boyi, Joy Ometere; van Schalkwijk, Linde; Tollenaar, Eveline A.P.; Gröne, Andrea; Wohlsein, Peter; Siebert, Ursula
Abstract: Whale lice (Cyamidae; Amphipoda) are ectoparasitic crustaceans adapted to the marine environment with cetaceans as their host. There are few reports of cyamids occurring in odontocetes from the North Sea, and long-term studies are lacking. Marine mammal health was monitored along the German and Dutch coasts in the past decades, with extensive post mortem investigations conducted. The aim of this study was to analyse archived ectoparasite samples from stranded cetaceans from the North Sea (2010–2019), to determine species, prevalence and impact of ectoparasite infection. Ectoparasites were found on two cetacean species – harbour porpoises ( Phocoena phocoena ), as the most abundant cetacean species in the North Sea, and on a pilot whale ( Globicephala melas ), as a rare species here. Prevalence of ectoparasitic crustaceans in cetaceans was low: 7.6% in porpoises stranded in the Netherlands (n = 608) and 1.6% in porpoises stranded in Germany (n = 122). All whale lice infections were found on hosts with skin lesions characterised by ulcerations. Morphological investigations revealed characteristic differences between the cyamid species Isocyamus (I.) delphinii and I. deltobranchium identified. Isocyamus deltobranchium was determined in all infected harbour porpoises. I. delphinii was identified on only the pilot whale. Molecular analyses showed 88% similarity of mDNA COI sequences of I. delphinii with I. deltobranchium supporting them as separate species. Phylogenetic analyses of additional gene loci are required to fully assess the diversity and exchange of whale lice species between geographical regions as well as host specificity. Differing whale lice prevalences in porpoises stranded in the Netherlands and Germany could indicate a difference in severity of skin lesions between these areas. It should be further investigated if more inter- or intraspecific contact, e.g., due to a higher density of porpoises or contact with other cetaceans, or a poorer health status of porpoises in the southern North Sea could explain these differences. Graphical abstract: Image 1 Highlights: First long term study of ectoparasitic crustaceans on North Sea odontocetes. Differences in prevalence in harbour porpoises between German and Dutch waters. Two cyamid species identified using morphological and molecular traits. associated to skin lesions in all investigated harbour porpoises and pilot whale. I. deltobranchium and I. delphinii closely related.